Chemical Constituents of Carissa opaca Extracts and Their Evaluation as Antioxidants and Preservatives in Edible Oils - AKMAL KHAN*, MUHAMMAD; SHAHWAR, DURRE; AHMAD, NAEEM; KHAN†, ZAHEER-UD-DIN; AJAIB†, MUHAMMAD (Asian Journal of Chemistry, 2009)
Carissa opaca (Stapf ex Haines) leaves were extracted using Soxhlet apparatus with petroleum ether (COE-PE), chloroform (COE-CH), ethyl acetate (COE-EA), acetone (COE-AC), methanol (COE-ME), n-butanol (COE-BU) and water (COE-WA). Antioxidant potential of Carissa opaca extracts (COEs) was evaluated by four methods: ferric thiocyanate, thiobarbituric acid, scavenging of DPPH• and total antioxidant capacity along with determination of total phenolics and antioxidant potential of COEs in peanut and sunflower oils. Results revealed that COEs had significant antioxidant potential (inhibition of lipid peroxidation > 50 %) and DPPH· scavenging potential (scavenging > 80 %). Moreover, total phenolic content was also higher in the extracts: COE-AC = 940 and COE-BU = 600 mg of gallic acid equivalents (GAE). Application of COEs as natural antioxidants in peanut and sunflower oils significantly reduced lipid peroxidation (inhibition > 60 %). A strong correlation of total phenols was observed with DPPH• and total antioxidant capacity assays (R2 = 0.9776 and R2 = 0.8104, respectively).